Catalogue of superfamily Pterophoroidea Kuznetsov & Stekolnikov (Lepidoptera) of India - Pathania, Prakash C.; Gielis, Cornelis; Das, Apurva; Chandra, Kailash (Zootaxa, 2021)
A catalogue of the species of superfamily Pterophoroidea from India is presented. The documented fauna comprises 108 species belonging to two families, Macropiratidae (one species), and Pterophoridae (107 species in 38 genera). Four subfamilies of Pterophoridae are recognized: i) Agdistinae (one species), ii) Deuterocopinae (five species in one genus), iii) Ochyroticinae (three species in one genus), and iv) Pterophorinae (98 species in 35 genera). The present catalogue is based primarily on the literatures in which Indian pterophoroids have been mentioned or described. For each species, the type-locality, geographical distribution (within and outside of India), host plants, and synonyms are provided. Pterophorus karmawangdi Gielis & Wangdi, syn. n., is new subjective junior synonym of Pterophorus tinsuki Kovtunovich, 2003.